High Frequency of Hemolysin Associated Genes among Staphylococcus Aureus Clinical Isolates in Iraq - Ali Jaffar Saleem (Journal of Global Pharma Technology, 2018)
AbstractIn current study, 120 clinical isolates of Staphylococcus aureus were collected from different hospitals in Diyala. In addtion of phenotypic method, all isolates diagnosed as S. aureus by genotypic method was done by Polymerase Chain Reaction (PCR) technique to detection nuc gene. PCR technique has been used to investigate hemolysin associated genes that encoding for hla, hlb, hlg and hld by using specific primers which showed the prevalence in percentage (95%, 79.17%, 90% and 96.67%) respectively. All isolates were found to be positive for at least two or more hemolysin genes and 69.17% of isolates were carrying all hemolysin genes.Keywords: Staphylococcus aureus, Thermo nuclease gene, Virulence genes, Alpha, Beta, Gamma and delta hemolysin.